Analisis Pelanggaran Etika dalam Praktik Akuntansi Keuangan: Studi Kasus PT. Maskapai Garuda Indonesia - Saridawati, Saridawati; Simamora, Rotua Tiofanta; Sembiring, Rhenda Basya (Innovative: Journal Of Social Science Research, 2024)
This study discusses the analysis of ethical violations in financial accounting practices using the case example of PT Garuda Indonesia Airline. In an increasingly complex era of globalization, ethics in financial accounting practices have become very important to ensure transparency and accountability of financial statements. Ethical violations in accounting can have fatal consequences, as seen in the Garuda Indonesia financial manipulation scandal. This research uses a qualitative approach with case analysis. Data was collected through pictures, words with primary and secondary sources related to the Garuda Indonesia financial manipulation scandal. Data analysis was conducted using descriptive analysis and interpretive analysis to identify themes and patterns related to ethical violations in financial accounting practices. This research shows that ethics in accounting is not only about complying with rules and regulations, but also about understanding and applying the moral principles that underlie accounting practices. Thus, this study hopes to raise awareness of the importance of ethics in financial accounting practices and reduce the likelihood of recurrence of similar cases in the future.